2017
DOI: 10.1002/14651858.cd012081.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological treatments for people with epilepsy

Abstract: Authors should strictly adhere to the CONSORT guidelines to improve the quality of reporting on their interventions. A thorough description of the intervention protocol is necessary to ensure reproducibility.When researching psychological treatments for people with epilepsy, the use of Quality of Life in Epilepsy Inventories (QOLIE-31, QOLIE-31-P, and QOLIE-89) would increase comparability. There is a critical gap in pediatric RCTs for psychological treatments, particularly those that use an epilepsy-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 116 publications
1
49
0
2
Order By: Relevance
“…Evidence based upon eight randomized control trials showed that psychological treatments (i.e. epilepsy education, nurse-led counselling, cognitive, memory and selfmanagement training, and cognitive behavioral and mindfulness therapy) enhanced emotional well-being in adults and adolescents with epilepsy [38]. Our finding that the mood of participants improved over time is similar to the attenuation of anxiety [39,40], and other forms of emotional distress [41], seen in those with acute stroke [40], newly diagnosed multiple sclerosis [39], and rheumatoid arthritis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence based upon eight randomized control trials showed that psychological treatments (i.e. epilepsy education, nurse-led counselling, cognitive, memory and selfmanagement training, and cognitive behavioral and mindfulness therapy) enhanced emotional well-being in adults and adolescents with epilepsy [38]. Our finding that the mood of participants improved over time is similar to the attenuation of anxiety [39,40], and other forms of emotional distress [41], seen in those with acute stroke [40], newly diagnosed multiple sclerosis [39], and rheumatoid arthritis [41].…”
Section: Discussionmentioning
confidence: 99%
“…31 A number of studies have examined epilepsy self-management interventions on mood outcomes and on quality of life. 28,32,33 The literature review by Smith and colleagues showed significant improvement in psychological outcomes in two of six studies. 34,35 The PACES epilepsy self-management intervention developed by Fraser and colleagues found a significant change in depressive symptom severity measured with the PHQ-9.…”
Section: Discussionmentioning
confidence: 99%
“…5 A recent Cochrane review found only moderate evidence supporting the effectiveness of psychological interventions for PwE. 6 Despite the availability of several potentially effective treatment options, depression and anxiety in PwE often remain underrecognized and undertreated. In particular, CBT is rarely available in epilepsy treatment settings.…”
Section: Introductionmentioning
confidence: 99%